Composite-alumina-carbon molecular sieve membranes prepared from novolac resin and boehmite. Part II: Effect of the carbonization temperature on the gas permeation properties - Margot A. Llosa Tanco (2015)
The influence of carbonization temperature on the permeation properties and aging of thin(4 mm) supported carbon molecular sieve membranes (c-CMSM), prepared from in housesynthesized novolac phenolic resin loaded with boehmite nanoparticles, were studied. Justafter membrane carbonization (fresh membrane), high permeance to N2 and O2 and low O2/N2 permselectivities were observed; the highest permeations were observed for carbonization end temperatures between 500 C and 700 C. After leaving the c-CMSM 1 day in theair, a large decrease in the permeation and considerable increase in the permselectivitywere observed due to the reduction of the pore size by oxygen chemisorption and waterphysical adsorption; the permeability to H2 and H2/N2 ideal permselectivity for a membrane carbonized at 550 C are close to palladium membranes for low temperature(<100 C). The effect of the permeation characteristics of the membranes carbonized atvarious temperatures and the removal of water adsorbed in the pores by heat treatmentwere studied.